Creating frames of practice for teacher education. Issue 2 (14th March 2016) - Burridge, Peter; Hooley, Neil; Neal, Greg
Abstract : Conceptualising teacher learning as being immersed in and arising from the totality of professional practice, this paper reports experiences and insights from practice-based teacher education. Initial data are drawn from two sites of seven involved in the federally funded School Centres for Teaching Excellence programme conducted in the state of Victoria, Australia. This programme is arranged as a partnership between the Department of Education and Early Childhood Development and various school clusters and universities. Each university is working with a cluster of primary and secondary schools and with large numbers (20–100) of pre-service teachers allocated to schools across each cluster. In general, PSTs in Victoria University's two clusters are placed at each school for 2 days per week with some block time throughout the year. Some university units of study are taught on-site by visiting lecturers with a strong emphasis being placed on the mentoring of PSTs by classroom teachers. Interviews with mentors/mentees and teachers, PSTs and principals indicate a particular understanding or approach to an issue of learning or relationship that provides a frame/scaffold of practice. Further practice begins to detail the frame for continuing application. We are considering the notion of frame as a conceptual skeleton of understanding that arises from school and classroom practice and is formatted in practice. Cases of practice have been reported in the paper below that indicate preliminary understandings and engagement with this concept for the learning of teachers.